Ponnana Muttai = The golden egg (Delhi, India : Manoj Publications, 2018)
The first story illustrates the evils of greed and the second illustrates the benefits of unity.
Keywords: Children's stories, Tamil; Tamil fiction; Folklore -- Juvenile literature